2014
DOI: 10.1111/bdi.12211
|View full text |Cite
|
Sign up to set email alerts
|

Minor physical anomalies in schizophrenia and bipolar I disorder and the neurodevelopmental continuum of psychosis

Abstract: Our findings support the existence of a continuum of neurodevelopmental adversity within the clinical spectrum of psychosis, with bipolar I disorder occupying an intermediate position between psychiatric health and schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…This showed that MPAs associated with schizophrenia are commonly found in the craniofacial region. This is in line with previous studies on the topography of MPAs in schizophrenia, 14 , 19–21 and is in support of the relation between early brain and craniofacial development. Minor physical anomalies in the craniofacial area can occur along with structural changes of the cerebrum in the intrauterine life of schizophrenics.…”
Section: Discussionsupporting
confidence: 93%
“…This showed that MPAs associated with schizophrenia are commonly found in the craniofacial region. This is in line with previous studies on the topography of MPAs in schizophrenia, 14 , 19–21 and is in support of the relation between early brain and craniofacial development. Minor physical anomalies in the craniofacial area can occur along with structural changes of the cerebrum in the intrauterine life of schizophrenics.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, very few studies have examined MPAs in BD or MDD. In direct comparisons between SCZ and bipolar I disorder, a study by Akabaliev, Sivkov, and Mantarkov () of MPAs rated using the Waldrop scale found intermediate scores in bipolar I disorder, while the highest scores were in SCZ, indicating that bipolar I disorder may occupy an intermediate position between the absence of a mental illness and SCZ. In particular, their study reported no difference in MPAs involving the eyes between patients with BD and controls, but a significant difference between those with SCZ and controls.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the case‐control ratio achieved in this study was 1:2.5. Similar, smaller, and larger samples of patients with schizophrenia were previously addressed in the scientific literature. Moreover, in contrast to the present study, specific samples had a control group even smaller than the case group .…”
Section: Discussionmentioning
confidence: 58%